EFFECT OF USING DIFFERENT TYPES OF ADDITIVES AGAINST THE COMPRESSIVE STRENGTH OF CEMENT PASTE - Jonbi; Wita Meutia; Nuryani Tinumbia; Farhan Rafliansyah (Jurnal Infrastruktur, 2022)
Cement as the main construction material is used for concrete, mortar and cement paste. Some problems with the use of cement are caused by shrinkage, cracking, so that these problems can reduce the compressive strength. This study analyzed the use of additives in overcome the weakness of cement paste. There are three types of additives used, namely, Intraplast Z, Cebex 100 and J-Additive. The percentages of additive use are 0.36%, 0.48%, 0.6% and 0.72% by weight of cement. The test object is a cube measuring 50 x 50 x 50 mm. The compressive strength test on cement paste was carried out at the age of 3, 7, 14 and 28 days. The results showed that for Intraplast Z and Cebex 100 the optimum percentage was 0.36% which resulted in an increase in compressive strength of 18% and 28%, respectively. As for the J-additive, there was an increase of 50% at a percentage of 0.36%. The benefits of the research resulted in the optimal percentage so that the use of additives became more efficient.